ANALISIS GAYA BAHASA IKLAN PADA SUPERMARKET EDISI RAMADHAN 2025 DI INSTAGRAM - Fitri, Najihatul; Haryadi, Rahmat Teguh; Aisyah, Nisa; Mahendra, Dede; Deswita, Deswita; Yuzdika, Reysa Anggraini; Yunindra, Wulan Tias (LPPM Universitas Nusa Mandiri, 2025)
The creative and attractive use of language to emphasize a product's uniqueness in advertising is known as the use of language style in advertisements. The aim of this research is to describe the language styles used in supermarket advertisements on Instagram during Ramadhan 2025. This research is a qualitative research. The data analyzed consists of sentences found in supermarket advertisements published on Instagram (March 1 - March 21, 2025). Data analysis applies the language style theory, which classifies four language styles: comparative, contradictory, associative, and repetitive. The findings of this study indicate that the most frequently used language style in supermarket advertisements on Instagram during Ramadhan 2025 is the contradictory style, followed by the comparative style, the repetitive style, and the associative style. From these findings, it can be seen that the use of language style in advertising plays a significant role in increasing both the visual and verbal appeal of a promotional message. The findings of this research are expected to contribute to subsequent studies focused on the analysis of language use in digital advertisements across various platforms and contexts.